Caloric Restriction and the Nutrient-Sensing PGC-1α in Mitochondrial Homeostasis: New Perspectives in Neurodegeneration. (8th July 2012) - Lettieri Barbato, Daniele; Baldelli, Sara; Pagliei, Beatrice; Aquilano, Katia; Ciriolo, Maria Rosa
Abstract : Mitochondrial activity progressively declines during ageing and in many neurodegenerative diseases. Caloric restriction (CR) has been suggested as a dietary intervention that is able to postpone the detrimental aspects of aging as it ameliorates mitochondrial performance. This effect is partially due to increased mitochondrial biogenesis. The nutrient-sensing PGC-1α is a transcriptional coactivator that promotes the expression of mitochondrial genes and is induced by CR. It is believed that many of the mitochondrial and metabolic benefits of CR are due to increased PGC-1α activity. The increase of PGC-1α is also positively linked to neuroprotection and its decrement has been involved in the pathogenesis of many neurodegenerative diseases. This paper aims to summarize the current knowledge about the role of PGC-1α in neuronal homeostasis and the beneficial effects of CR on mitochondrial biogenesis and function. We also discuss how PGC-1α -governed pathways could be used as target for nutritional intervention to prevent neurodegeneration.